HEADLINES AND THEIR FUNCTIONS IN PRESENT-DAY POLITICAL DISCOURSE OF MASS MEDIA - Danylenko, O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
This paper considers headlines of German-language news articles and their functions in present-day political discourse of mass media. The concept of "political communication" is specified and the main target trends in studying news headlines from a linguistic point of view are interpreted. The headline is a text sign with a very strong effect, it has the following characteristics: informativeness, modality, formal construction and semantic completeness, interpretability, polyfunctionality. The high tempo and the level of the IT development change the manner of presenting material by focusing mostly on the readers of Internet news to whom of special importance is the degree of the newness of some information or the special viewpoint under which an information event is covered. The data for research within the framework of this paper are the headlines of articles with political news on the Deutsche Welle website. To reveal the mechanism of the influence of headlines on political discourse construction, special attention is paid to their functional and structural peculiarities in contemporary media space. The main structural types of news headlines are two-member sentences, headlines in the form of questions, elliptical headlines and nominative headlines difering from each other in the manner of presenting information. The prevailing structural pattern of the headline in the German-language press is a two-member sentence with a direct word order, the number of the words varying from six to eight. In the course of the analysis of news headlines the most typical functions are described: nominative-informative, graphically-highlighting, informational, influencing, advertising and evaluative-expressive as well as integrative and searching functions of headlines. Briefness and structural rigidity are characteristic of German-language news articles. The following principles are typical of the news articles on the Deutsche Welle website: intensified visualization, strongly pronounced interactivity, simplicity and promptness.